Emigrantes 2.0: Ucranianos online em tempo de guerra - Caseiro, Margarida (Trabalhos de Antropologia e Etnologia, 2020)
Taking the separatist conflict that started in Eastern Ukraine in April 2014, this article approaches the centrality of the Internet in contemporary migrant communities and how this fact has opened up new ethnographical possibilities. This paper focuses on a group of Ukrainians using Facebook as an instrument of affirmation against secessionism and of civic and political participation within their country, from Portugal. The social network materializes these migrants’ transnational experience (Basch et al. 2005 [1994]) who are able to find in online spaces a platform where to express their “imagined community” (Anderson 1991).